Trends of Traditional Culinary Tourism Research in Tourism Sector Journals Around Indonesia - I Made Darsana; Putu Herny Susanti (Budapest International Research and Critics University, 2022)
This research aims tocollect information on various studies that discuss traditional culinary tourism in Indonesia. Using content analysis that focuses on the findings of various studies that have been published in scientific journals in Indonesia. The trend found was an increase in the number of publications with the topic of traditional culinary tourism as a major concern in the last five years. Most quantitative research is found. The island of Java is the most frequently used location compared to other islands in Indonesia. In addition, traditional culinary business actors were mostly chosen as research subjects, while the most widely applied data collection technique was survey. Descriptive statistics is a data analysis technique that dominates traditional culinary tourism research articles.